2017
DOI: 10.1136/heartasia-2017-010884
|View full text |Cite
|
Sign up to set email alerts
|

Non-compaction of left ventricular myocardium in sub-Saharan African adults

Abstract: Contrary to previous beliefs, NCLV may not be less common in black Africans than in other ethnic subgroups. Clinicians in Africa should be made aware of NCLV so that it can be diagnosed at earlier stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This review identified underlying etiologies of SCA/SCD and ventricular arrhythmias in SSA, with hypertensive heart disease, coronary disease, cardiomyopathy, including peripartum cardiomyopathy, and valvular heart disease, especially rheumatic heart disease being the most common causes of SCA/SCD among adults [ 61 64 67 69 71 72 73 90 ]. Others include malignant arrhythmogenic inherited diseases [ 74 75 76 77 78 79 80 81 84 85 86 87 88 102 103 104 ], pericarditis [ 92 ], endemic parasitic infections [ 9 93 ], pulmonary embolism [ 62 91 ], endomyocardial fibrosis [ 95 ], congenital heart disease [ 96 ], pulmonary embolism [ 62 91 ], pulmonary hypertension [ 61 ], and aortic dissection/rupture [ 64 ]. Despite sarcoidosis being prevalent in SSA where approximately one in five cases is often mis-diagnosed as tuberculosis, studies on cardiac manifestations of sarcoidosis are lacking in this region [ 102 103 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified underlying etiologies of SCA/SCD and ventricular arrhythmias in SSA, with hypertensive heart disease, coronary disease, cardiomyopathy, including peripartum cardiomyopathy, and valvular heart disease, especially rheumatic heart disease being the most common causes of SCA/SCD among adults [ 61 64 67 69 71 72 73 90 ]. Others include malignant arrhythmogenic inherited diseases [ 74 75 76 77 78 79 80 81 84 85 86 87 88 102 103 104 ], pericarditis [ 92 ], endemic parasitic infections [ 9 93 ], pulmonary embolism [ 62 91 ], endomyocardial fibrosis [ 95 ], congenital heart disease [ 96 ], pulmonary embolism [ 62 91 ], pulmonary hypertension [ 61 ], and aortic dissection/rupture [ 64 ]. Despite sarcoidosis being prevalent in SSA where approximately one in five cases is often mis-diagnosed as tuberculosis, studies on cardiac manifestations of sarcoidosis are lacking in this region [ 102 103 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, studies in African Americans have shown that the relatively high prevalence of ER in this population is not independently predictive of adverse outcomes [82,83]. Ventricular non-compaction, a prominent cause of VT/VF, has been identified in patients of African ancestry with the prevalence of 6.9% in one cardiomyopathy clinic in South Africa [84], and in other SSA studies [85,86]. Apart from one case report in a black infant [87], no other studies have documented congenital long QT syndrome in Black Africans.…”
Section: Reported Underlying Etiologies Of Sca/scd and Ventricular Armentioning
confidence: 99%
“…NCLV is characterized by prominent left ventricular trabeculae and deep inter-trabecular recesses (94). It is not as rare as once believed, with documented reports from different African countries since 2006 (105).…”
Section: Other Cardiomyopathiesmentioning
confidence: 99%
“…These baseline characteristics were comparable to those of other single‐center, multicenter, or different regional studies. 9 , 10 , 11 , 12 , 13 , 14 A total of 10.5% of the patients were asymptomatic at presentation, and they were usually identified after referral because of the presence of cardiac abnormalities on routine physical examination. Notably, the mean time from the onset of symptom to the correct diagnosis was 2.52 years.…”
Section: Discussionmentioning
confidence: 99%